2012
DOI: 10.1177/0022022112466944
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Cross-Cultural Competence

Abstract: The present study was designed to assess the viability of developing quantitative measures of cross-cultural competence as an emergent organizational-level construct using samples of military organizations. Cross-cultural competence has predominantly been discussed as an individual-level construct but has not been extensively assessed as an organizational-level phenomenon. A synthesis of the cross-cultural competence, organizational intelligence, and multilevel analysis literatures was used to construct a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 89 publications
0
21
0
1
Order By: Relevance
“…Champions of cultural competence or, in other words, influential leaders in cultural competence have been recommended as organizational strategies to support the development of cultural competence at the organizational level ( Chrisman, 2007 ). Despite this acknowledgment of the importance of organizational factors, there have been very few empirical studies assessing the practical effects of such organizational factors on cultural competence ( van Driel & Gabrenya, 2013 ). To our knowledge, our study is one of the first to assess the influence of the cultural competence of leaders on the cultural competence of the healthcare staff.…”
Section: Discussionmentioning
confidence: 99%
“…Champions of cultural competence or, in other words, influential leaders in cultural competence have been recommended as organizational strategies to support the development of cultural competence at the organizational level ( Chrisman, 2007 ). Despite this acknowledgment of the importance of organizational factors, there have been very few empirical studies assessing the practical effects of such organizational factors on cultural competence ( van Driel & Gabrenya, 2013 ). To our knowledge, our study is one of the first to assess the influence of the cultural competence of leaders on the cultural competence of the healthcare staff.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a low-OCQ organization might fail to train employees to display basic cultural etiquette, resulting in awkward cultural gaffes when meeting local clients. Research shows that OCQ can aid strategic efforts given demonstrated relationships with increased international strategic alliances (Yitman, 2013) and perceived organizational effectiveness and cohesion (van Driel & Gabrenya, 2013).…”
Section: Targeted Organizational Support As a Shrm Interventionmentioning
confidence: 99%
“…Researchers established some support for a two-factor model, despite inherent methodological challenges that limited the utility of the scale. Van Driel's research was extended by van Driel and Gabrenya (2013) with four studies. In each, they used individual-level data to assess organizational-level phenomenon.…”
Section: Intelligence At the Organizational Levelmentioning
confidence: 99%
“…van Driel and Gabrenya (2013) The organization actively seeks cultural knowledge 17. Moon (2010) The organization has a process in place to facilitate cultural learning 18.…”
Section: Emerging Itemsmentioning
confidence: 99%
See 1 more Smart Citation